Measurement of the t̄t production cross section in the all-jet final state in pp collisions at √s=7 TeV - Chatrchyan, S. (2013)
A measurement is presented of the t̄t production cross section σt̄t in proton-proton collisions at a centre-of-mass energy of 7 TeV, in the all-jet final state that contains at least six jets, two of which are tagged as originating from b quarks. The data correspond to an integrated luminosity of 3.54 fb-1, collected with the CMS detector at the LHC. The cross section is determined through an unbinned maximum likelihood fit of background and t̄t signal to the reconstructed mass spectrum of t̄t candidates in the data, in which events are subjected to a kinematic fit assuming a t̄t → W+bW-̄b → 6 jets hypothesis. The measurement yields σt̄t = 139±10(stat.)±26(syst.)±3(lum.)pb, a result consistent with those obtained in other t̄t decay channels, as well as with predictions of the standard model. © 2013 CERN for the benefit of the CMS collaboration.